Tissue- and liquid-biopsy based NGS profiling in advanced non-small-cell lung cancer in a real-world setting: the IMMINENT study - Sposito, Marco; Belluomini, Lorenzo; Nocini, Riccardo; Insolda, Jessica; Scaglione, Ilaria Mariangela; Menis, Jessica; Simbolo, Michele; Lugini, Antonio; Buzzacchino, Federica; Verderame, Francesco; Spinnato, Francesca; Aprile, Giuseppe; et al. (Frontiers in Oncology, 2024)
To date, for all non-small cell lung cancer (NSCLC) cases, it is recommended to test for driver alterations to identify actionable therapeutic targets. In this light, comprehensive genomic profiling (CGP) with next generation sequencing (NGS) has progressively gained increasing importance in clinical practice. Here, with the aim of assessing the distribution and the real-world frequency of gene alterations and their correlation with patient characteristics, we present the outcomes obtained using FoundationOne (F1CDx) and FoundationLiquid CDx (F1L/F1LCDx) NGS-based profiling in a nationwide initiative for advanced NSCLC patients.F1CDx (324 genes) was used for tissue samples, and F1L (70 genes) or F1LCDx (324 genes) for liquid biopsy, aiming to explore the real-world occurrence of molecular alterations in aNSCLC and their relationship with patients' characteristics.Overall, 232 advanced NSCLC patients from 11 Institutions were gathered [median age 63 years; never/former or current smokers 29.3/65.9%; adenocarcinoma/squamous 79.3/12.5%; F1CDx/F1L+F1LCDx 59.5/40.5%]. Alterations were found in 170 different genes. Median number of mutated genes per sample was 4 (IQR 3-6) and 2 (IQR 1-3) in the F1CDx and F1L/F1LCDx cohorts, respectively. TP53 (58%), KRAS (22%), CDKN2A/B (19%), and STK11 (17%) alterations were the most frequently detected. Actionability rates (tier I and II) were comparable: 36.2% F1CDx vs. 34% ctDNA NGS assays (29.5% and 40.9% F1L and F1LCDx, respectively).Alterations in KEAP1 were significantly associated with STK11 and KRAS, so as TP53 with RB1. Median tumor mutational burden was 6 (IQR 3-10) and was significantly higher in smokers. Median OS from metastatic diagnosis was 23 months (IQR 18.5-19.5) and significantly lower in patients harboring ≥3 gene mutations. Conditional three-year survival probabilities increased over time for patients profiled at initial diagnosis and exceeded those of individuals tested later in their clinical history after 12 months.This study confirms that NGS-based molecular profiling of aNSCLC on tissue or blood samples offers valuable predictive and prognostic insights.